Premarital self-disclosure predicting distal marital outcomes - Schachtner, Laura (Kansas State University, 2017)
Can having more frequent conversations with a romantic partner prior to marriage contribute to better marital outcomes several years into a marriage? Little is known regarding premarital self-disclosure and its association with distal marital outcomes. Data was utilized from 707 newly married couples assessed across the first four years of marriage through three waves of assessment as part of the Marriage Matters Panel Survey of Newlywed Couples (Nock, Sanchez, & Wright, 2008). Structural equation modeling, including common-fate analysis, was used to test self-disclosure prior to marriage and its association with later marital quality of each spouse and the odds of divorce or separation by the first four years into marriage. Couple-level reactivity was tested as a mediator of these associations, while controlling for known covariates. Results indicated that premarital self-disclosure was associated with wives’ higher marital satisfaction and lower odds of divorce or separation three to four years into marriage. This relationship was mediated by reactivity. Clinical implications are discussed for couples prior to marriage, suggesting more frequent conversations about a wider variety of topics between dating couples.
Keywords: marital satisfaction; marital stability; premarital discussion content; self-disclosure; separationdivorce